Rancang Bangun Aplikasi Inventory Barang Pada Tempat Food and Drink Berbasis Android - Mohammad Taufan Asri Zaen; Yuliadi Yuliadi; Nora Dery Sofya; Hammid Muammar Robbani Al Faruq (STMIK Budi Darma, 2021)
TEMPAT FOOD AND DRINK is a micro, small and medium enterprise in the culinary field which has two outlets in Sumbawa. TEMPAT FOOD AND DRINK selling cold drinks and foods. Recording was done manually, by the Production Manager notes on a mobile phone or a piece of paper or by keeping a purchase note. In one day there can be 4 to 5 transactions in and out of goods with various types and the number of goods reached tens of pieces from the warehouse or shop carried out by the Production Manager. This research aims to make it easier for Production Managers to calculate the number of available items in a warehouse or store, make it easier to be able to reorder with an android-based inventory. Waterfall is a system development method used in this research. The Unified Model Language (UML) used for system design is use case diagrams, activity diagrams, sequence diagrams, and class diagrams and the programming language used is Java. The result of this research is an android-based inventory application for TEMPAT FOOD AND DRINK that could find out the number of available items. Application tested with whitebox testing shows success on each independent path of the existed flowgraph